Dynamical Behavior of Brusselator System Driven by Non-Gaussian Noise - Dong , Qiang; Guo , Yongfeng (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
The non-Gaussian noise induced the mean first passage time (MFPT) in Brusselator system are examined. In this paper, the path integral method is used to approximate non-Gaussian noise to Gaussian color noise. The FPT of the 50000 response tracks is obtained by solving the system equation through the fourth-order stochastic Runge-Kutta algorithm. Then we get the MFPT. The influences of the noise intensity, correlation time and non-Gaussian parameter of non-Gaussian noise on the MFPT are characterized. We also found the noise enhanced stability (NES) phenomenon in the system.